Plate 4 from Amphitheatrum Sapientiae Aeternae, Solius, Verae [Amphitheatre of the Only True Eternal Wisdom] - Khunrath, Heinrich (Amphitheatrum Sapientiae Aeternae Solius Verae, 1609)
Plate 4 of Khunrath Heinrich's (1560-1605) Amphitheatrum Sapientiae, purportedly one of the most significant books of theosophical alchemy and the occult sciences. Though the title page reads 1602, the book was not published until 1609. Erasmus Wohlfahrt edited and published the manuscript following Heinrich's death in 1605. Wohlfahrt also added a preface and conclusion. The work contains masterful engravings, remarkable for their execution as well as alchemical symbolism. Nine double-paged copperplate engravings, a title page, and a frontispiece can be found in the digital collections. A circular engraving. At the center is a depiction of Jesus, "Veré filius dei erat ipse," "He was truly the son of God."
Keywords: Alchemy; Christian art and symbolism; Theosophy; Engraving--Printing; Alchemy--Religious aspects; Alchemy in art; Occultism